The Brilliant Legacy of Islam in Andalusia 711–1492: The Influence of Islamic Civilization's Golden Age on Europe's Renaissance - Ainiyah, Mahfudhoh; Setiawan, Agus Mahfudin (El Tarikh : Journal of History, Culture and Islamic Civilization, 2024)
This study examines the heyday of Islamic civilization in Andalusia and its influence on the rise of Europe through a historiographic approach. By highlighting the timeline of advanced civilization in Andalusia and the backward conditions in Christian Europe, this study shows how advances in education, culture, and scientific innovation in Andalusia, such as in Cordova, Granada, and Seville, have had a significant impact on Europe. By conducting a strategic analysis of figures who played a role in the Islamic civilization period in Andalusia, starting from invasions, glory, to decline. Using historical methods through primary sources from historical figures such as Philip Khuri Hitti and Reinhart Dozy, this study provides an in-depth picture of the transfer of science and culture from the Islamic world to Europe. This article reveals how the intellectual contributions of Islamic scholars in Andalusia from various fields of scholarship later became an inspiration and bridge to the revival of intellectual and cultural life in Europe during the Renaissance. Thus, this study offers a new perspective on the important role of Islamic civilization in forming the foundation for the rise of Europe.